THEORETICAL ANALYSIS OF THE RELATIONSHIP BETWEEN THE ELECTRONIC STRUCTURE AND ITS INHIBITORY ACTION IN THE P2X7R RECEPTOR OF A SERIES OF 2-HYDROXY-1,4-NAPHTHOQUINONES DERIVATIVES - Soloaga Ardiles, Carlos; Cárcamo Vega, José (Journal of the Chilean Chemical Society, 2019)
In this work, a theoretical study of the relationship between the electronic structure and the activity of the P2X7R receptor from 2-hydroxy-1,4-naphthoquinone derivatives, using the KPG method, was performed. The electronic structure of the molecules was calculated at level B3LYP / 6-31G (d, p) with full geometry optimization. A statistically significant equation was obtained by relating the variation of biological activity with the variation of a set of indices of local atomic reactivity. Based on the analysis of the results, a two-dimensional pharmacophore was proposed.